How general conditions affect regional innovation systems: The case of the two Germanys - Michael Fritsch; Holger Graf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We compare two leading regional innovation systems (RIS) in East Germany with two RIS in West Germany of about the same size and internal settlement structure. Our analyses show that differences in the performance between the regions cannot easily be related to the structural properties of the respective innovation networks because divergent general economic conditions in the two parts of the country as well as the integration of regions into their neighboring spatial environment play a rather dominant role. Overall, our analysis clearly shows that an analysis of RIS should account for the general economic conditions as well as for the position of a region in its spatial environment. Focusing just on the respective region is not enough.
Keywords: O31; Z13; R11; 330; regional innovation systems; national innovation systems; innovator networks; gatekeeper; social network analysis; Forschungskooperation; Performance-Messung; Vergleich; Soziales Netzwerk; Neue Bundesländer; Alte Bundesländer; Deutschland